Maternal body mass index and the risk of early-onset Group B Streptococcus disease in newborns: A systematic review and meta-analysis - Elisabeth Emanuel Graae; Niels Uldbjerg; Flemming Skjøth; Marie Aunskjær Bech; Pernille Nathalie Nielsen; Susani Rothmann Karkov; Caroline Margaret Moos; Mohammed Rohi Khalil (PLoS ONE, 2026)
Background Early-onset group B Streptococcus disease (EOGBS) remains a leading cause of neonatal morbidity and mortality. The incidence can be substantially reduced by intrapartum antibiotic prophylaxis in women with defined risk factors. However, the role of high prepregnancy body mass index (BMI) as a risk factor remains unclear. This systematic review and meta-analysis therefore aimed to evaluate the association between maternal BMI and the risk of EOGBS, as well as related proxy outcomes, including intrapartum vaginal GBS colonization and rectovaginal or urinary GBS colonization before term. Methods We systematically searched MEDLINE, Embase, and Cochrane CENTRAL on the 28 th of January 2026, for studies examining the relationship between pregestational BMI and EOGBS or its proxy outcomes. Eligible studies included observational and interventional designs but not case reports and conference abstracts. Risk of bias was assessed using the QUIPS tool. Random-effects meta-regression and sensitivity analyses were performed. Results We identified 19 eligible observational studies reporting data from a total of 3,707,047 women, encompassing 277,887 cases. For the risk of EOGBS and its proxy outcomes, assuming a log-linear association, our meta-regression showed a 2.4% increase in the odds ratio (OR) per unit increase in BMI. This corresponds to an OR of 1.4 (95% CI 1.1–1.6) for a BMI of 35 and 1.7 (95% CI 1.3–2.3) for a BMI of 45, compared to a normal BMI of 22.3. One very large study on 1,971,346 live singleton births with 780 EOGBS cases, found a hazard ratio of 2.4 (95% CI 1.7–3.4) for a BMI of 35.0–39.9 compared to normal BMI (18.5–24.9). Conclusions Although the overall association appears modest, incorporating BMI may improve prevention strategies for EOGBS .